Ablation for Mitral Valve Patients With AF Successfully Controls Heart Rhythm - Coltrera, Francesca (MD Conference Express, 2015)
In this Cardiothoracic Surgical Trials Network study assessing freedom from atrial fibrillation at both 6 and 12 months, carefully selected mitral valve surgery patients (7.5% of screened patients) were randomized to surgery alone or plus ablation via pulmonary vein isolation or biatrial maze. The ablation group had higher rates of heart rhythm control but also higher rates of pacemaker implantation than anticipated.